PENGARUH HARGA MINYAK DUNIA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA (MODERASI VARIABEL MONETER) - Sari, Wilda Novita; Ariusni, Ariusni (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
Abstract: The purpose of this research is to be able to determine the effect of world oil prices on economic growth in Indonesia by applying the exchange rate moderating variable and the BI rate as a connecting variable. Descriptive and associative research is a type of research that is used with data collection techniques through a trusted official agency website that is classified in the quarterly time series secondary data. The data year in this study was from 2006 to 2018. Data analysis was carried out through descriptive and inductive analysis with a Moderated Regression Analysis (MRA) data analysis tool accompanied by a classic assumption test and a t test. Estimation results show that there are two research results; firstly, that the exchange rate has an effect on moderating the relationship between world oil prices and economic growth in Indonesia, secondly, that the BI rate has no influence connecting world oil prices and economic growth in Indonesia.Â Keywords: World oil prices, economic growth, exchange rates, BI rate, Moderated Regression Analysis (MRA).